Flexible energy-efficient and direct intra-ODN/OPN communication capable TWDM PON architecture with centralized OLT sharing among multiple optical networks - Garg, Amit Kumar; Janyani, Vijay; H. Aly, Moustafa; Zainol Abidin, N. H.; Mustapha Kamil, Yasmin; Radhouene, Massoudi (Academic Press, 2022)
Nowadays, service reliability, operation cost, transmission latency of optical access networks are the major challenging issues that need to be addressed while planning and developing the next-generation passive optical networks (NG-PONs). This paper proposes a flexible, energy-efficient, time and wavelength division multiplexed (TWDM) PON architecture that has the capability of centralized optical line terminal (OLT) resource sharing with multiple optical networks. The architecture has the point-to-point direct inter-optical networking unit (dedicated inter-ONU) transmission capability among the various ONUs located within the same optical distribution network (ODN). Such transmission may also be referred to as direct intra-ODN communication. The architecture also has the potential of transmitting an inter-ONU signal to the ONUs residing in the different ODNs (inter-ODN) belonging to the same optical network (OPN). Such transmission may be referred as the direct inter-ODN or intra-OPN transmission. The architecture reduces the normalized energy consumption of approximately 2.21875 Wh per hour, normalized transmission latency of approximately 148 µs for the direct inter-ONU transmission. This is achieved by diverting the inter-ONU signal from the remote nodes (RNs) itself towards the intended ONUs. The percentage energy saving of the proposed architecture is approximately 74 % as compared to the conventional architecture. The proposed architecture is suitable for strengthening the existing information and communication technology (ICT) infrastructures and can be implemented in next-generation flexible, energy-efficient, latency-aware, and reliable optical networks for developing smart rural and urban communities.